Occasional deconstructions - Wolfreys, Julian, 1958- (Albany : State University of New York Press, 2004)
"In Occasional Deconstructions, Julian Wolfreys challenges the notion that deconstruction is a critical methodology, offering instead a number of reintroductions or reorientations to the texts of Jacques Derrida and the idea or possibility of deconstructions. Proceeding from specific readings of various texts (both film and literary), as well as mobilizing a number of issues from Derrida's recent work surrounding questions of ethics, politics, and identity, Wolfreys considers the role of deconstruction in broader academic and institutional contexts, and questions whether, in fact, deconstruction can be called upon to function as theory at all."--Jacket
Reflecting on the occasions of introduction : justifying the unjustifiable or, beginning again -- Uncanny temporalities, haunting occasions : Sunset boulevard -- Biography's ruins : the afterlife of Mary Shelley -- Between : speculations -- Eternity and a day or, an "Endless forward" : Tout dire -- Citation's haunt : spectres of Derrida -- Occasions of trauma and testimony : witnessing, memory, and responsibility -- Origins of deconstruction : deconstruction, that which arrives (if it arrives at all) -- Hauntology or the political? : (or, no politics, not now) : always already deceived -- Letter to Martin McQuillan, concerning "the New International" : the indelible Marx of haunting -- Guilty reading.
Includes bibliographical references (pages 355-370) and index.
Print version record.
JSTOR
Keywords: Deconstruction; Literature, Modern -- History and criticism; Deconstructivism (Architecture); Déconstruction.; Déconstructivisme (Architecture); Deconstructivist; deconstruction (theory); TRAVEL -- Special Interest -- Literary; LITERARY CRITICISM -- General; Deconstruction; Literature, Modern; Criticism, interpretation, etc